Edu-game Application Based-Android Quantity and Unit Concepts Using Game Engine Constructs 2 - Nur Khoiri; Wahyu Adien Perdana; Wijayanto (Postgraduate, University of Mataram, 2023)
The purpose of this research is to produce alternative learning media about understanding the concept of unit size as an interactive and fun educational tool. This research uses the Research and Development (R&D) method and the product development model uses the MDLC (Multimedia Development Life Circle)) consisting of six stages, namely concept, design, material collecting, assembly, testing, distribution. The media expert validation test concluded that media expert 1 with an average percentage of 77% included the criteria of